2003
DOI: 10.1021/cc020071p
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Lead Optimization of [1,2]-Diamines Based on Ethambutol as Potential Antituberculosis Preclinical Candidates

Abstract: Despite relatively modest potency, ethambutol (EMB, (S,S)-[N,N-di-2-amino-1-butanol]ethylenediamine) is a mainstay of contemporary chemotherapy for the treatment of tuberculosis. We have developed a solid-phase synthesis of 1,2-diamine analogues of EMB using a novel acylation-reduction sequence that is compatible with high-throughput 96-well format chemistry. Using this procedure, we have synthesized 63 238 diamine analogues in pools of 10 that are suitable for testing. MIC and a target-based reporter assay we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
160
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 32 publications
3
160
0
Order By: Relevance
“…The activity against Gram-positive bacteria has been reported also for the adamantyl derivatives of oxadiazoles, thioureas and thiadiazoles. 25,26,29 However, the activity data are not comparable since different activity tests were employed. 33 Adamantyl derivative of Platensimycin was found also as extremely potent against Gram-positive methicillinresistant Staphylococcus aureus (MRSA) exhibiting activity in the range 1-2 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The activity against Gram-positive bacteria has been reported also for the adamantyl derivatives of oxadiazoles, thioureas and thiadiazoles. 25,26,29 However, the activity data are not comparable since different activity tests were employed. 33 Adamantyl derivative of Platensimycin was found also as extremely potent against Gram-positive methicillinresistant Staphylococcus aureus (MRSA) exhibiting activity in the range 1-2 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
“…21 Characterization of product 24 compares well with literature (mp = 103-105°C). 21 (25) was prepared from 24 by treatment with BBr 3 in 79 % yield according to the published procedure. 21 Characterization of product 25 compares well with literature (mp = 155-157°C).…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation
“…It was the most potent compound (MIC = 0.1-0.63 μg/mL) in the series (Lee et al, 2003). In vivo studies showed 1 to 2.0-log reduction in CFU counts in the lung and spleen at 25 mg/kg.…”
Section: Sq-109mentioning
confidence: 95%
“…SQ109 hinders the action of MmpL3, an essential membrane protein which transport trehalose monomycolate into the cell envelope. So it inhibits genesis of mycolic acid of cell wall instead of inhibiting arabinosyl transferase which is the prime action ethumbutol [39][40][41][42].…”
Section: New Drugs Approvedmentioning
confidence: 99%